Simulated learning environment (SLE) in audiology education: a systematic review - Dzulkarnain, Ahmad Aidil Arafat; Wan Mohd Pandi, Wan Mahirah; Rahmat, Sarah; Zakaria, Nur 'Azzah (Informa Health Care, 2015)
Objective: To systematically review the relevant peer-review literature investigating the outcome of simulated learning environment (SLE) training in audiology education. Design: A systematic review research design. Study sample: Fifteen databases were searched with four studies meeting the inclusion criteria. Results: Three of the four studies revealed positive findings for the use of an SLE (that is, the SLE group showed a higher post-training score compared to the traditional training group or a significantly higher post-training score than the non-training groups). One study revealed negative findings where the traditional training group showed a significantly higher post-training score than the SLE group. In addition, both the studies comparing post- and pre-training scores reported significantly higher post-training scores than the pre-training scores of the participants that underwent SLE training. Conclusions: Overall, this review supports the notions that SLE training is an effective learning tool and can be used for basic clinical training. This conclusion should be treated with caution, considering the limited numbers of studies published in this area and future research should be conducted to cope with the gaps highlighted in this review.